Microsimulation Population Projections with SAS A Reference Guide - Marois, Guillaume; KC, Samir; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2021)
This open access book provides a step-by-step overview on how to build a microsimulation model with SAS. It shows how to convert an already existing multistate projection by age, sex, education and region into a microsimulation model. Two new dimensions are then added, either the labor force participation and the sector of activity, and/or some examples of outputs and alternative scenarios that would not be possible with standard demographic methods. The book also describes how to adapt the model for other countries or other purposes. It also provides details on how to extend and adapt the model for other purposes as well as other use of microsimulation with SAS. The book suggests codes that are easy to understand, so they can be replicated or adapted for other purposes. As such, this book provides a great resource for people with beginner to intermediate knowledge in SAS.
Chapter 1. Introduction -- Chapter 2. Getting Started -- Chapter 3. Converting a Cohort Component Model into a Microsimulation Model -- Chapter 4. Adding New Dimensions -- Chapter 5. Building Alternative Scenarios -- Chapter 6. Extending and Adapting the Model -- Chapter 7. Conclusion.
Keywords: Demography; Population; Computer simulation; Population and Demography; Computer Modelling